Association between HLA‐B1502 Allele and Antiepileptic Drug‐Induced Cutaneous Reactions in Han Chinese - Man, Celeste B.L.; Kwan, Patrick; Baum, Larry; Yu, Evelyn; Lau, K.M.; Cheng, Alice S.H.; Ng, Margaret H.L. (Epilepsia (Copenhagen), 2007)
A previous study conducted in Taiwan found a 100% association between HLA‐B*1502 allele and carbamazepine‐induced Stevens‐Johnson syndrome (SJS) in Han Chinese subjects, with an extremely high odds ratio compared with carbamazepine‐tolerant subjects (odds ratio = 2,504). We examined this association in 24 Hong Kong Han Chinese subjects who had cutaneous adverse reactions induced by different antiepileptic drugs (AEDs). They were matched with 48 AED‐tolerant controls. HLA‐B*1502 was associated with severe cutaneous reactions (SCR) induced by AEDs, which included carbamazepine, phenytoin, and lamotrigine (p = 0.001, odds ratio = 17.6), but was not associated with maculopapular exanthema (MPE) (p = 0.32). Further studies in larger samples of ethnically matched subjects should be conducted to confirm the findings. Identification of genetic polymorphisms predisposing to development of AED‐induced SCR offers the possibility of avoiding these high‐risk drugs in genetically susceptible individuals.